2011
DOI: 10.1007/s11745-011-3548-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Enhances Arachidonic Acid Metabolites in a Growth Hormone Transgenic Mouse

Abstract: In a transgenic growth hormone (GH) mouse model, highly elevated GH increases overall growth and decreases adipose depots while low or moderate circulating GH enhances adipose deposition with differential effects on body growth. Using this model, the effects of low, moderate, and high chronic GH on fatty acid composition were determined for adipose and hepatic tissue and the metabolites of 20:4n-6 (arachidonic acid) were characterized to identify metabolic targets of action of elevated GH. The products of Δ-9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…In our study, tilapia fed with the A233 supplemented diet also showed a significantly lower content of 18:1n‐9 (principal MUFA) in both liver and muscle; moreover, the total MUFA level was statically lower in this group. A similar pattern was observed for the hepatic lipid profile of GH transgenic mice, where the activity of Δ‐9 desaturase was found to decrease in response to a high level of circulating GH, as indicated by the decreased level of lipid (Oberbauer et al, ).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…In our study, tilapia fed with the A233 supplemented diet also showed a significantly lower content of 18:1n‐9 (principal MUFA) in both liver and muscle; moreover, the total MUFA level was statically lower in this group. A similar pattern was observed for the hepatic lipid profile of GH transgenic mice, where the activity of Δ‐9 desaturase was found to decrease in response to a high level of circulating GH, as indicated by the decreased level of lipid (Oberbauer et al, ).…”
Section: Discussionsupporting
confidence: 66%
“…In GH transgenic mice, a high level of circulating GH changes the FA composition toward a more unsaturated profile (Oberbauer et al, ), reduced essential precursors of long‐chain PUFA (LN and ALA), and increased levels of desaturation and elongation products ARA and DHA, indicating increased activity of the D5D and D6D enzymes (Murray et al, ). In our study, the EPA, DPA, and DHA content and composition increased in both liver and muscle, possibly related to a higher level of circulating GH due to the inclusion of A233 in the diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SCD products and FADS2 mRNA have also recently been shown to be induced by GH in mice [44]. The change in expression of these enzymes could be a possible link between acromegaly and insulin resistance due to an elevation of unsaturated fatty acids, as activity of FADS1 and FADS2 are associated with metabolic syndrome [45,46].…”
Section: Resultsmentioning
confidence: 99%